KONSUMSI KOPI MENURUNKAN RISIKO KEJADIAN PENYAKIT KARDIOVASKULAR - Winnie Nirmala Santosa; Ummy Maisarah Rasyidah; Anita Dahliana; Dwi Martha Nur Aditya; Achmad Hendra Hartawan Wawan (Fakultas Kedokteran Universitas Alkhairaat, 2024)
Background: Coffee is among the most popular beverages worldwide and contain substantial amounts of caffeine, making caffeine themost widely consumed psychoactive agent. Apart from being a psychoactive stimulant, it turns out that caffeine has a positive potential for caffeine in reducing the incidence of diseases in the cardiovascular system. Objective: Analyze the benefits of coffee on the cardiovascular system. Method: An examination and analysis of research findings from literature searches are done both nationally and internationally using PubMed databases and Google Scholars in a literature review using a narrative methodology. Results: Caffeine increases the release of endothelial nitric oxide, diminishes insulin sensitivity, regulates lipogenesis less tightly, and possesses antioxidant qualities that can minimize the risk of cardiovascular disease. Conclusion: Coffee gives positive benefits to the cardiovascular system.